Surface-active lipid linings under shear load: a combined in-situ neutron reflectivity and ATR-FTIR study - Schwörer, Felicitas; Trapp, Marcus; Ballauff, Matthias; Dahint, Reiner; Steitz, Roland (Langmuir, 2015)
We study shear effects in solid-supported lipid membrane stacks by simultaneous combined in-situ neutron reflectivity (NR) and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). The stacks mimic the terminal surface-active phospholipid (SAPL) coatings on cartilage in mammalian joints. Piles of 11 bilayer membranes of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) are immobilized at the interface of the solid silicon support and the liquid D2O backing phase. We replace the natural hyaluronic acid (HA) component of synovial fluid by a synthetic substitute, namely, poly(allylamine hydrochloride) (PAH), at identical concentration. We find the oligolamellar DMPC bilayer films strongly interacting with PAH resulting in a drastic increase of the membranes d spacing (by a factor of ∼5). Onset of shear causes a buckling-like deformation of the DMPC bilayers perpendicular to the applied shear field. With increasing shear rate we observe substantially enhanced water fractions in the membrane slabs which we attribute to increasing fragmentation caused by Kelvin-Helmholtz-like instabilities parallel to the applied shear field. Both effects are in line with recent theoretical predictions on shear-induced instabilities of lipid bilayer membranes in water (Hanasaki, I.; Walther, J. H.; Kawano, S.; Koumoutsakos, P. Phys. Rev. E 2010, 82, 051602). With the applied shear the interfacial lipid linings transform from their gel state Pβ′ to their fluid state Lα. Although in chain-molten state with reduced bending rigidity the lipid layers do not detach from their solid support. We hold steric bridging of the fragmented lipid bilayer membranes by PAH molecules responsible for the unexpected mechanical stability of the DMPC linings.